PENGARUH KINERJA LAYANAN, KEPERCAYAAN DAN KEPUASAN TERHADAP LOYALITAS KONSUMEN DALAM MENGGUNAKAN JASA PENGIRIMAN BARANG - Wahyu Nugroho, Adi; Sudaryanto, Budi (Diponegoro Journal of Management, 2013)
The background to the problem, that the various efforts made by the company are not offsetby increased sales. The results of the field survey showed that in the last three years of customerloyalty to the service delivery HIRA Cargo Semarang branch decreased. This study aims todetermine and describe the effect of service performance, reliability and customer satisfaction tocustomer loyalty in using freight forwarder Cargo Branch at Hira SemarangPopulation of the research are a HIRA Cargo consumers who are still actively using theHIRA freight Cargo Branch Semarang until October of 2012. Data collection is done usingquestionnaires. The analysis including validity and reliability, the assumption test, test hypothesesthrough F test and t test, coefficient of determination (R2). Data analyze techniques using linearregression analysis.Hypothesis testing using t test showed that the three independent variables studied wereservice performance (X1), trust (X2), and customer satisfaction (X3) have significantly affect to thedependent variable, customer loyalty (Y). Then through the F test showed that the variables serviceperformance, trust, and customer satisfaction have a significant effect in Customer loyalty.Adjusted R Square proving that the customer loyalty variables can be explained by three variablesservice performance, trust, and customer satisfaction.